Corporate social responsibility and CEO confidence - McCarthy, Scott; Oliver, Barry; Song, Sizhe (Journal of Banking & Finance, 2017)
This study examines the relationship between firm corporate social responsibility (CSR) and CEO confidence. Research shows that CSR has a hedging feature. Research also shows that more confident CEOs underestimate firm risks, which, in turn, leads them to undertake relatively less hedging. Consistent with this, we find that CEO confidence is negatively related to the level of CSR. Closer analysis shows that this effect is stronger in the institutional aspects of CSR, such as community and workforce diversity, rather than in the technical aspects of CSR, such as corporate governance and product quality. Our results are robust to different competing explanations, including narcissism, which refers in this context to CEOs who engage in CSR to attract attention and alternative proxies for CSR and CEO confidence.